Intelligent SERS Navigation System Guiding Brain Tumor Surgery by Intraoperatively Delineating the Metabolic Acidosis (Adv. Sci. 7/2022). Issue 7 (4th March 2022) - Jin, Ziyi; Yue, Qi; Duan, Wenjia; Sui, An; Zhao, Botao; Deng, Yinhui; Zhai, Yuting; Zhang, Yuwen; Sun, Tao; Zhang, Guang‐Ping; Han, Limei; Mao, Ying; et al.
Abstract : Surgery Navigation System Surgeons face challenges in defining brain tumor margins due to its infiltrative nature. In article number 2104935 by Ying Mao, Jinhua Yu, Xiao‐Yong Zhang, Cong Li, and co‐workers, an intelligent SERS navigation system is developed to intraoperatively guide tumor resection by delineating the metabolic acidosis without the administration of exogenous probes. Considering the correlation between tissue acidity and malignancy, this system holds the promise in improving surgical prognosis by precisely defining tumor infiltrative regions.